Tribological behaviour of 3 d-printed poly(lactic) acid - polycarbonate urethane polymer blend for artificial articular cartilage - Shaharuddin, Shanahs (2024)
In order to better understand the tribological behaviour of a poly(lactic) acid (PLA)-polycarbonate urethane (PCU) blend for artificial articular cartilage applications, this study investigates the blend's composition, which is 90 wt.% PLA-10 wt.%PCU. Layer thicknesses of 0.10, 0.12, 0.14, and 0.16 mm were used when printing the samples. All the samples were put through a ball-on-disc tribo-test in which a normal load of 30, 50, and 70 N was applied. Ringer's lactate served as a lubricant and the simulating the environment in vivo. The hardness, contact angle, surface roughness, and surface morphology tests were also used to analyse the 3D-printed samples. Based on these tests, 3D-printed samples with 0.16 mm layer thickness outperform other samples with different viscosities of Ringer's lactate, regardless of the applied normal load during the tribo-test. The results showed that the PLA-PCU polymer blend was well suited for artificial articular cartilage applications due to its favourable tribological characteristics, including a lower friction coefficient of around 0.10 and wear rate of around 1x10-3mm3/Nm when tested with highest viscosity of Ringer’s lactate of 1.52mPa.s. PLA's mechanical integrity and wear resistance were enhanced by the addition of PCU, increasing PLA's durability. Additionally, the addition of Ringer's lactate enhanced the polymer blend's tribological performance, indicating its compatibility with the natural joint environment. By shedding light on the tribological behaviour of PLA-PCU polymer blends 3D printed for artificial articular cartilage, this work paves the way for future developments in additive manufacturing and biomaterial design. The findings are a promising first step toward creating durable prosthetic joint implants that will enhance mobility and quality of life for individuals with joint disorders.